NISAN KUNO DI JAILOLO: BUKTI PERKEMBANGAN ISLAM ABAD KE-18 DI MALUKU UTARA - Laila Abdul Jalil (BRIN, 2017)
Moluccas Islands which is rich of spices has become an appeal for the foreign trades to come make a trades of spices. The first foreign traders who visited the Moluccas Island are muslim Arab traders. The entry of Islam into Jaillolo is marked by the existence of ancient gravestone in the Village of Galala and Gam Lamo. This paper aims to describe the process of entry through the variatons of ancient gravestone in Jailolo. This preliminary study used descriptive method of analysis.